EXPERIMENTAL STUDY OF SULPIRIDE TOXICITY AT DIFFERENT FORMS OF ITS INTAKE INTO THE BODY - Горохова, Лариса Геннадьевна; Корсакова, Татьяна Георгиевна; Логунова, Татьяна Дмитриевна (Medicine in Kuzbass, 2019)
Subject of the study. Sulpiride toxicity at different forms of its intake into the body. The objective of the study was an experimental study on the risk of intoxication in various forms of sulpiride intake into the body. Materials and methods. The toxicity indicators of sulpiride were studied. Experimental toxic and hygienic studies were carried out on outbred white mice and rats, rabbits, guinea pigs and dogs. The functional organ state was assessed by a complex of biochemical, physiological, hematological and morphological indices. During inhalation exposure, the concentration of substances in the air of the priming chambers was determined spectrophotometrically. Statistical data processing was performed using the program «Statistic for Windows 10.0». Main results. The average lethal dose of sulpiride, when introduced into the stomach, for female rats was 6000 mg/kg, for male rats – 7200 mg/kg, for female and male mice – 2300 and 3400 mg/kg, respectively. It belongs to the substances of the III-IV classes of danger. Intraperitoneal average lethal dose was 220 mg/kg for male rats and 150 mg/kg was for female rats. The threshold of acute inhalation action was 63.5 mg/m3. The study medication had a marked ability to cumulation, the cumulation coefficient was 2.9. No immunotoxic, mutagenic and embryotoxic action was detected in sulpiride. It did not have a local irritant effect on the skin. Skin resorptive and sensitizing effects were not detected. It caused mild irritant effect on mucous membranes of eyes. It had a toxic effect on the central nervous system tissue and hepatorenal system. Conclusions. The results of experimental studies allow us to classify sulpiride as moderately hazardous and low-hazard substances (III-IV hazard classes) with no reliably significant differences in the parameters of species and sexual sensitivity. The conducted toxicological and hygienic studies allowed calculating and proposing the value of the tentative safe level of exposure in the air of the working area at the level of 0.5 mg/m3. Compliance with these standards in the workplace can minimize the risk to the health of workers.